2005
DOI: 10.1071/rdv17n2ab137
|View full text |Cite
|
Sign up to set email alerts
|

137 Effect of Flunixin Meglumine in Co-Culture Medium on the Development of in Vitro Matured and Fertilized Bovine Embryos

Abstract: PG concentration is often increased during uterine manipulation with embryo transfer. Embryo viability is affected by the increase in the PGF2α concentration accompanying manipulation of the uterus during embryo transfer. Schrick et al. (2001 Theriogenology 55, 370 abst) observed that treatment with flunixin meglumine, an inhibitor of prostaglandin, increased pregnancy rates depending on the stage and quality of embryos transferred. On the other hand, prostaglandin was secreted by a cumulus cell monolayer in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In agreement with our results, Goda et al. () showed that the developmental rate of blastocysts was moderately increased compared with the control when embryos at the same developmental stage were treated with an identical concentration of FM that was used in this study. Another report showed a decrease in the percentage of blastocysts when a higher concentration of FM was used at an earlier stage of bovine embryo development (zygote) (Razza et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results, Goda et al. () showed that the developmental rate of blastocysts was moderately increased compared with the control when embryos at the same developmental stage were treated with an identical concentration of FM that was used in this study. Another report showed a decrease in the percentage of blastocysts when a higher concentration of FM was used at an earlier stage of bovine embryo development (zygote) (Razza et al.…”
Section: Discussionsupporting
confidence: 93%
“…Embryos at the eight and/or beyond cell stage were cultured in IVC-II (BSA was replaced with 10% (v/v) FBS in IVC-I) with 5 ng/ml FM, 1 ng/ml PGF 2 a or a combination of 5 ng/ml FM and 1 ng/ml of PGF 2 a for 5 days. The final concentrations of FM and PGF 2 a were selected on the basis of previous publications (Scenna et al 2004a;Goda et al 2005). This experiment was performed 11 independent times.…”
Section: In Vitro Production (Ivp) Of Bovine Embryosmentioning
confidence: 99%